Nano-Cerium: A Promising Additive for Enhancing Cryosurvival and Antioxidant Defence in Buffalo Bull Semen - Chaudhari, Meet T; Parmar, Kiran H; Patel, Richakumari M; Pathan, Mohsin M; Chaudhari, Dinesh V; Parmar, Jignesh J; Hadiya, Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was aimed to evaluate the effect of cerium oxide nanoparticles (CeO2NPs) supplementation in Tris-fructose-yolk glycerol (TFYG) extender on post-thaw semen quality of buffalo bulls. Semen ejaculates (n=18) collected from four healthy, sexually mature bulls using an artificial vagina were pooled and divided into four treatment groups containing 0 (control), 25, 50, and 75 μg/ mL CeO2NPs in TFYG extender. The samples were processed, equilibrated, cryopreserved, and evaluated post-thaw for sperm motility, viability, morphology, plasma membrane integrity, acrosome integrity, malondialdehyde (MDA), and total antioxidant capacity (TAC). Post-thaw sperm motility was significantly higher (p<0.05) in extender supplemented with 50 and 75 μg/mL CeO2NPs compared to 25 μg/mL and control groups, while 75 μg/mL CeO2NPs showed a marked improvement in sperm viability and reduced sperm abnormalities compared to other treatments. The extender with 75 μg/mL CeO2NPs also maintained significantly better sperm plasma membrane and acrosome integrity than the lower concentrations and control. Moreover, the MDA level was significantly reduced (p<0.05) and TAC was increased in semen supplemented with 75 μg/mL CeO2NPs, indicating enhanced antioxidant protection and reduced oxidative stress during cryopreservation. It is concluded that supplementation of TFYG extender with 75 μg/mL cerium oxide nanoparticles is optimal for maintaining superior post-thaw sperm quality by improving structural and functional attributes as well as antioxidant status in buffalo bull semen, though further in vivo fertility trials are required to confirm these findings.